The determinants of financial literacy among students at Universiti Utara Malaysia - Abdul Rahman, Raouf Al-Samarraie (2021)
This research attempts to investigate the key determinants of financial literacy among young adults studying in a university in the northern region of Malaysia. Besides, this research will investigate the influence of financial behaviour on financial literacy. This study would also examine the influence of gender differences and having financial knowledge basics on financial literacy among the students. The financial literacy competency of these students will be evaluated based on their financial awareness, financial behaviour, financial attitude, financial knowledge, and financial skills. The justification for this selection is due to time and location constraint. Since this is a final year project paper and the study is conducted during the MCO (Movement Control Order) period, the researcher must resort to an online platform for data collection. Online questionnaires were developed using Google form and then distributed based on convenience - which includes individuals who happen to be easily accessible to the researcher. The total number of usable responses received after the data collection process was 537 respondents. This study concludes four key determinants of financial literacy among Malaysian youths – awareness, behaviour, attitude, and knowledge. Subsequently, this study corresponds to others by supporting the existing ideas that gender differences and basic financial knowledge have a certain degree of impact on financial literacy. This study is important to understand the key determinants of financial literacy among young adults studying in a university in the northern region of Malaysia. Efforts may be taken to strengthen those variables to increase the literacy rate among the students in other universities in Malaysia.